Sub-angstrom noninvasive imaging of atomic arrangement in 2D hybrid perovskites - Telychko, Mykola; Edalatmanesh, Shayan; Leng, Kai; Abdelwahab, Ibrahim; Guo, Na; Zhang, Chun; Mendieta-Moreno, Jesús I; Nachtigall, Matyas; Li, Jing; Loh, Kian Ping; Jelínek, Pavel; Lu, Jiong (Science advances, 2022)
Noninvasive imaging of the atomic arrangement in two-dimensional (2D) Ruddlesden-Popper hybrid perovskites (RPPs) is challenging because of the insulating nature and softness of the organic layers. Here, we demonstrate a sub-angstrom resolution imaging of both soft organic layers and inorganic framework in a prototypical 2D lead-halide RPP crystal via combined tip-functionalized scanning tunneling microscopy (STM) and noncontact atomic force microscopy (ncAFM) corroborated by theoretical simulations. STM measurements unveil the atomic reconstruction of the inorganic lead-halide lattice and overall twin-domain composition of the RPP crystal, while ncAFM measurements with a CO-tip enable nonperturbative visualization of the cooperative reordering of surface organic cations driven by their hydrogen bonding interactions with the inorganic lattice. Moreover, such a joint technique also allows for the atomic-scale imaging of the electrostatic potential variation across the twin-domain walls, revealing alternating quasi-1D electron and hole channels at neighboring twin boundaries, which may influence in-plane exciton transport and dissociation.